Technologies for quality improvement and diversification of jute - Bhaduri, S K; Debnath, S; Satapathy, K K (Indian Farming, 2015)
Technologies have been developed through sustained R & D activities for improvement in quality of jute by improved retting process and its application in diversified nontraditional fields with value-addition besides the traditional packaging sector. Jute-based geotextiles and agrotextiles have potential applications in soil conservation and crop production opening an avenue for utilization of jute in large quantities. Blending of manmade fibre with jute introduces some improved properties, like bulk, elongation, regularity, luster etc. which can produce yarns by different technologies developed at NIRJAFT for making furnishing fabric, dress materials, warm clothes etc. Handicrafts, handmade paper, handbags and soft luggage, handloom weaving, etc. are some of the technologies suitable for adopting in rural areas. Most of these technologies do not require sophisticated costly equipments rather simple, robust and labour intensive and are promising for creating employment opportunities and income generation by small entrepreneurship in the rural sector.